PEMBERDAYAAN KELOMPOK IBU-IBU PKH DALAM PEMBUATAN MAKANAN SEHAT DI KAMPUNG BULANG KOTA TANJUNGPINANG - Solina, Emmy; Syafitri, Rahma; Elsera, Marisa; Rahmawati, Nanik; Taufiqurrahman, Taufiqurrahman; Anggriawan, Dedi (Universitas Sahid, 2023)
Program Keluarga Harapan (PKH) is provided by the government for poor families as an effort to accelerate poverty reduction. The Bulang Village area will receive PKH as many as 270 families in 2021. Those who received assistance formed a KUBE (Kelompok Usaha Bersama) group in the form of a home industry. The methods used are socialization and training, discussion and practice or simulation with a participatory approach. This activity provides training and knowledge about healthy food preparations which usually use sugar which is now replaced with honey. Because the gluten content in sugar is very high which will cause diabetes. The aim is to develop the home industry, it is hoped that it can become a job opportunity, especially for housewives, in an effort to improve the social welfare of the family. The products that will be produced are processed foods made from bananas which will be made into banana cakes, crispy bananas and banana nuggets. The result is increased knowledge, skills, health, economy and independence for PKH members.